Damage Control Surgery (DCS) Problems on Severe Abdominal Trauma (SAT) in the Emergency Installation - Harahap, Sabasdin; Pusponegoro, Aryono Djuned (Riviera Publishing, 2022)
Introduction: Based on the division of the anatomical region of the body, the abdominal region is the third most frequently traumatized region, which is about 8% of all trauma cases. At RSUPN CM Jakarta, abdominal trauma ranks second after the head and neck region as a cause of death due to trauma. This study aims to determine the problems in the DCS action on the SAT. Provide objective data regarding issues in DCS actions on SAT at the ER at the CM Hospital. Method: This study uses a retrospective study method with a descriptive study. The number of samples used is the total population observed. Result: 4 factors influencing mortality from severe trauma, namely; (1). The degree of severity of the trauma, (2). Host factor (host), (3). When definitive action is taken, and (4). Quality of trauma care. Of the four factors, only factors 3 and 4 can be handled in the ER of the CM Hospital, while factors 1 and 2 are factors beyond the hospital's reach. Trauma management in pre-hospital care requires a more comprehensive approach for medical personnel who assist patients and their families. Five of the 6 cases carried out by DCS died. Whereas the Ps value of the 6 cases is more than 50%. This can describe the condition of handling DCS in SAT patients at CM Hospital is not good. Conclusion: The condition of DCS handling in SAT cases is influenced by pre-hospital care, treatment in the ER, surgical techniques and treatment in the ICU. Pre-hospital care for the 6 cases was very slow, DCS decisions were not on site, operating techniques did not pay attention to triad of death indicators and handling in the ICU was less integrated with other departments.